DEVELOPMENT OF HUMAN RESOURCE COMPETENCIES TO IMPROVE THE QUALITY OF REPUBLIC SERVICES AT THE DIRECTORATE GENERAL OF RELIGIOUS COURTS BODY - Refa Annisa Handayani; Tarisni Sevty Bahri; Fatimatuzzahra (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to examine the implementation of human resource competency development at the Directorate General of Religious Courts (Ditjen Badilag), identify the obstacles encountered in its implementation, and find solutions to these obstacles in order to improve the quality of public services, particularly the One-Stop Integrated Service (PTSP). This study employs a descriptive qualitative approach, using data collection techniques that include face-to-face interviews with Human Resources Managers, as well as a review of documents comprising official information from the Ditjen Badilag website and service data from the Badilag PTSP for the period January–April 2026. The research results indicate that the internal, needs-based human resource competency development program—which includes technical and functional training for service managers—has had a positive impact on improving the quality of public services. This is reflected in the rising scores of the Public Satisfaction Survey (SKM) and the Employee Satisfaction Survey (SKP), which demonstrate positive evaluations from both the public and internal staff regarding the quality of the PTSP within the Directorate General of Badilag. Furthermore, the agency achieved the Corruption-Free Zone (WBK) designation in 2020 and the Clean and Service-Oriented Bureaucracy Zone (WBBM) designation in 2021. The success is supported by legalization service data, which show that an average of 99.5% of legalization requests were processed on the same day as the filing date. However, implementation still faces three common challenges: budget constraints, time constraints due to employees’ operational workloads, and the misalignment of training participants with program objectives. In response to these challenges, the agency has implemented solutions such as optimizing training through online platforms, coordinating schedules more intensively from the planning stage, and refining the participant selection process based on profile alignment and competency needs.